OPTIMALISASI PELAKSANAAN BIMBINGAN KONSELING OLEH GURU KELAS BAGI PESERTA DIDIK SEKOLAH DASAR DI KOTA BOGOR - Mulyawati, Yuli; Hikmah, Nur; Wijaya, Ade (STKIP Subang, 2021)
This study aims to see the optimization of counseling guidance by classroom teachers in elementary schools in the city of Bogor as the executor of counseling guidance that seeks to overcome the problems experienced by students in learning. The research method used in this study is a qualitative research method, which is naturalistic research because in carrying out the research it is carried out in natural conditions following the reality in the field. This research was carried out at SDN Bantar Jati 9 Kota Bogor in grade 3, totaling 25 people, the class teacher was Mrs. Ely Rahmawati. The results of the research based on the results of the questionnaire are that it can be seen that there is an even assessment in the teacher's statement guiding so that students can accept every weakness they have, from these results provide a different rater for each child. In the results of the interview with the 3rd-grade teacher at SDN Bantar Jati 9 Kota Bogor, several things were conveyed regarding the counseling guidance carried out by him, including guiding, reminding, giving advice, giving punishment, correcting, providing motivation, and giving examples. Optimization of the implementation of counseling guidance by classroom teachers can be carried out including by guiding students to pray before learning and after carrying out learning activities, Teachers guide students to become independent children, Teachers tell students about how to behave politely, politely to teachers and peers, teachers guide students to be responsible when they make mistakes, teachers guide students to have empathy for others, teachers give explanations about how to learn well and effectively, teachers guide students to calm down in preparing themselves facing the test, the teacher motivates students to continue to be enthusiastic in learning. Based on this, the implementation of counseling guidance by classroom teachers in elementary schools in the city of Bogor can be concluded to be carried out optimally.